Rekayasa Sosial melalui Kelompok Usaha Bersama (KUBE) di Desa Sungai Pitung, Kalimantan Selatan - Branden Jaya Tivantara; Bartoven Vivit Nurdin; Ifaty Fadliliana Sari; Damar Wibisono (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
The implementation of the Hasnur Centre Foundation Knitting KUBE in Sungai Pitung Village to create an economic ecosystem. The researcher used a social engineering study to analyze the implementation of the Knitting KUBE. The method used in this research. This research uses a qualitative method with a descriptive approach. Data collection techniques used were participant observation, in-depth interviews, and documentation. The results showed that there was social mapping and stakeholder coordination, group formation and capacity strengthening, and stakeholder coordination, group formation and capacity building, and action evaluation in the implementation of the Knitting KUBE by the Hasnur Centre Foundation. Social engineering improves the skills of its members and creates economic opportunities. However, there is a need to understand the characteristics of the community to prevent dependency on the program. With that, cultural development is needed to realize the mindset and cultural values of an advanced society. That is advanced. The discourse on cultural development can be translated through government policy by maximizing stakeholder collaboration in implementation.